2002
DOI: 10.1164/rccm.200108-007oc
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution from Traffic and the Development of Respiratory Infections and Asthmatic and Allergic Symptoms in Children

Abstract: Despite the important contribution of traffic sources to urban air quality, relatively few studies have evaluated the effects of traffic-related air pollution on health, such as its influence on the development of asthma and other childhood respiratory diseases. We examined the relationship between traffic-related air pollution and the development of asthmatic/allergic symptoms and respiratory infections in a birth cohort (n approximately 4,000) study in The Netherlands. A validated model was used to assign ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
350
5
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 575 publications
(397 citation statements)
references
References 41 publications
32
350
5
10
Order By: Relevance
“…Though many studies of the chronic health effects associated with long-term exposure to air pollution (often from large, well-known cohorts) examine the use of an alternative exposure metric in an epidemiologic study (Adar et al 2013;Brauer et al 2002;Jerrett et al 2008;Puett et al 2011;Young et al 2014;Zmirou et al 2004), only the seven studies found by the authors and described below examine multiple approaches to exposure assessment, and include comparison of the epidemiologic results obtained when using each exposure metric. However, many manuscripts lacked definitive conclusions about which exposure metric was most beneficial, and the wide range of health outcomes, exposure metrics, and exposure durations of interest used make it difficult to draw larger conclusions from these studies.…”
Section: Studies Of Chronic Health Effects Associated With Long-term mentioning
confidence: 99%
“…Though many studies of the chronic health effects associated with long-term exposure to air pollution (often from large, well-known cohorts) examine the use of an alternative exposure metric in an epidemiologic study (Adar et al 2013;Brauer et al 2002;Jerrett et al 2008;Puett et al 2011;Young et al 2014;Zmirou et al 2004), only the seven studies found by the authors and described below examine multiple approaches to exposure assessment, and include comparison of the epidemiologic results obtained when using each exposure metric. However, many manuscripts lacked definitive conclusions about which exposure metric was most beneficial, and the wide range of health outcomes, exposure metrics, and exposure durations of interest used make it difficult to draw larger conclusions from these studies.…”
Section: Studies Of Chronic Health Effects Associated With Long-term mentioning
confidence: 99%
“…The literature examining the effects of motor vehicle emissions on respiratory and cardiovascular health is extensive (e.g., Ku¨nzli et al, 2000;Brauer et al, 2002Brauer et al, , 2007Brunekreef and Holgate, 2002;Hoek et al, 2002a, b;Gauderman et al, 2005;Krzyzanowski et al, 2005;Wilhelm and Ritz, 2005). Geographic estimates of ambient concentration distributions enable assessment of within-city variability of traffic-related pollutants for epidemiological studies of their health impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that children who live near traffic have greater symptoms and increased hospitalizations for asthma (Edwards et al, 1994, Brauer et al, 2002. The severity of asthma symptoms is also associated with ambient benzene concentrations (Thompson et al, 2001;Delfino et al, 2003).…”
Section: Introductionmentioning
confidence: 99%